Consumer Protection of After-Sales Service for Discontinued Motor Vehicle Brands in Indonesia - Safira Maharani; Andry Setiawan (Faculty of Law, Universitas Negeri Semarang, 2025)
One of the important components of consumer rights protected by Law Number 8 of 1999 concerning Consumer Protection is after-sales service, such as the availability of spare parts and repair services. Consumers can suffer losses due to the loss of access to these services when the manufacturer or official distributor ceases operations. Consumer rights that should be obtained often cannot be fully implemented and fulfilled. Consumers are often the most disadvantaged parties due to the negligent practices of companies. By examining case studies of car manufacturers that have ceased operations in Indonesia, this study uses a juridical-empirical methodology. Based on the research findings, consumers are in a weak position to obtain protection or compensation due to the legal vacuum. Therefore, it is necessary to strengthen regulations and long-term responsibility mechanisms from business actors to ensure the continuity of after-sales services even though the business entity has ceased operations.